Murine model and mechanisms of treatment-induced painful diabetic neuropathy. (23rd June 2017) - Nicodemus, Juliet M.; Enriquez, Cynthia; Marquez, Alexandra; Anaya, Carlos J.; Jolivalt, Corinne G.
Highlights: Insulin induces neuropathic pain in high-fat diet mice. Insulin-induced pain is independent of glucose levels. Our murine model of treatment-induced neuropathy of diabetes provides evidence for an insulin-IGF1 pathway-based mechanism. Abstract: Diabetes mellitus represents a group of metabolic diseases that are characterized by hyperglycemia caused by either lack of insulin production or a reduced ability to respond to insulin. It is estimated that there were 347 million people worldwide who suffered from diabetes in 2008 and incidence is predicted to double by 2050. Neuropathy is the most common complication of long-term diabetes and approximately 30% of these subjects develop chronic neuropathic pain. A distinct acute, severe form of neuropathic pain, called insulin neuritis or treatment-induced painful neuropathy of diabetes (TIND), may also occur shortly after initiation of intensive glycemic control, with an incidence rate of up to 10.9%. The pathological mechanisms leading to TIND, which is mostly unresponsive to analgesics, are not yet understood, impeding the development of therapies. Studies to date have been clinical and with limited cohorts of patients. In the current study, we developed chronic and acute insulin-induced neuropathic pain in mice with type 2 insulin-resistant diabetes. Furthermore, we determined that insulin-induced acute allodynia is independent of glycemia levels, can also be induced with Insulin-like Growth Factor 1 (IGF1) and be prevented by inhibition of AKT, providing evidence of an insulin/IGF1 signaling pathway-based mechanism for TIND. This mouse model is useful for the elucidation of mechanisms contributing to TIND and for the testing of new therapeutic approaches to treat TIND.